Effect of polidocanol foam sclerotherapy for the treatment of venous ulcers: a randomized clinical trial protocol - de Moraes Silva, Melissa Andreia (2025)
Objective: To evaluate the effect of polidocanol foam sclerotherapy in patients with venous ulcers (VU) undergoing clinical treatment with elastocompression. Method: This will be a randomized, prospective, single-center, exploratory clinical trial with two parallel groups and 1:1 allocation. Participants aged 18-80 years with active VU and vascular Doppler ultrasound findings indicating chronic superficial venous insufficiency in both sexes will be included. Participants will be randomized into two groups: the Clinical group (undergoing conservative treatment with elastocompression) and Foam group (undergoing treatment of varicose veins with polidocanol foam associated with elastocompression). Thirty-four patients will be selected for each group. Participants in the Foam group will undergo superficial vein sclerotherapy using the Tessari technique, with the aid of ultrasound. Patients will be reassessed 30, 90, and 180 days after the intervention. The primary outcome will be lesion healing within 180 days. The secondary outcomes will be the VU healing time, rate of lesion area reduction, side effects, pain, quality of life (QOL) using the EQ-5D, and the Venous Clinical Severity Score. The data will be subjected to inferential tests and Kaplan-Meier survival analysis, assuming a significance level of 5%.